Cutaneous ulcer in an immunosuppressed patient with adult onset Still's disease: primary cutaneous histoplasmosis? - Michelle Larissa Zini Lise; Ronaldo Nunes Godinho; Flávia Moojen Brollo; Henrique Luiz Staub (Sociedade Brasileira de Dermatologia, 2014)
Histoplasmosis is caused by the dimorphic fungus Histoplasma capsulatum.Primary infection occurs through inhalation of spores from the air. Immunocompetent individuals are usually asymptomatic, but may develop pulmonary disease. Immunocompromised patients tend to present systemic histoplasmosis with cutaneous lesions occurring by secondary invasion. In this case report, we describe a probable primary cutaneous histoplasmosis (PCH) in a patient with adult onset Still's disease under immunosuppression.